Dispersal of alien invasive species on anthropogenic litter from European mariculture areas. (June 2018) - Rech, Sabine; Salmina, Simone; Borrell Pichs, Yaisel J.; García-Vazquez, Eva
Abstract: The importance of mariculture areas for the dispersal of alien invasive species (AIS) on artificial floating items has recently been highlighted as a priority research need. Here we present the results of surveys in two important European shellfish culture areas that release rafting AIS, the Venetian lagoon and the Portuguese Algarve region. We found eight aquaculture-related non-native, invasive species attached to anthropogenic litter items mostly related to aquaculture: Amphibalanus amphitrite, Austrominius modestus, Balanus trigonus, Hesperibalanus fallax, Hydroides elegans, Hydroides sanctaecrucis, and Magallana angulata . These species are well-adapted to rafting on artificial surfaces and have a high potential to disperse via this vector. This is the first record of the notorious nuisance species H. sanctaecrucis both in the Mediterranean and Eastern Atlantic, as well as on floating litter. We also present the first records of M. angulata, H. sanctaecrucis, Sabellaria alveolata, Mytilus edulis and Chthamalus montagui on stranded anthropogenic litter. Highlights: Fouled anthropogenic litter was sampled on beaches in two aquaculture regions. Eight aquaculture-related non-native fouling species were identified. First record of Hydroides sanctaecrucis in the Mediterranean and East-Atlantic.